2010
DOI: 10.1007/s10531-010-9801-5
|View full text |Cite
|
Sign up to set email alerts
|

Identifying key environmental factors related to plant and crustacean assemblages in Mediterranean temporary ponds

Abstract: The current interest in Mediterranean temporary wet habitats, considered to be habitats of European Community Interest, is mainly due to their characteristic flora and fauna. Several contributions characterize each of these two components separately, but considering them simultaneously could reveal possible interactions and a more complete view of the habitat that would be useful to improve conservation measures. This paper investigates crustacean and plant assemblages in six Mediterranean temporary ponds and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 58 publications
3
31
2
Order By: Relevance
“…In contrast to submerged macrophyte coverage, hydrophyte richness did not significantly differ between plateau and mountain ponds nor was it related to altitude in spite of the wide elevation range (1420 m), well above that in some previous studies (Bagella et al, 2010). Our results seem to challenge the widespread opinion that altitude is a major environmental driver of macrophyte richness (e.g.…”
Section: Hydrophyte Richnesscontrasting
confidence: 86%
“…In contrast to submerged macrophyte coverage, hydrophyte richness did not significantly differ between plateau and mountain ponds nor was it related to altitude in spite of the wide elevation range (1420 m), well above that in some previous studies (Bagella et al, 2010). Our results seem to challenge the widespread opinion that altitude is a major environmental driver of macrophyte richness (e.g.…”
Section: Hydrophyte Richnesscontrasting
confidence: 86%
“…Apart from this calanoid, other accompanying taxa were also rare and of biogeographical interest such as the large branchiopods: Branchipus cortesi, an Iberian endemic, or the western-Mediterranean Maghrebestheria maroccana (Sahuquillo & Miracle, 2010). Moreover, uncommon taxa and high species richness have been reported in other ponds where Hemidiaptomus occurs (Gauthier, 1928;Alonso, 1987;Marrone & Naselli Flores, 2004;Alonso & Garcia-de-Lomas, 2009;Caramujo & Boavida, 2010), not only for crustaceans but also for plants (Bagella et al, 2010). These Hemidiaptomus ponds are a refuge for several peculiar species, suggesting the existence of a former and ancient wetland area with sufficiently low historical disturbance to maintain a complexly structured crustacean community.…”
Section: Special Ponds With Hemidiaptomus: the Role Of Historical Facmentioning
confidence: 81%
“…The group of species H. ingens, found in these ponds, is very rare with very few known localities, and in the Iberian Peninsula, it has been found only in the ponds of this study. Moreover, uncommon taxa and high species richness have been reported in other ponds where Hemidiaptomus occurs (Gauthier, 1928;Alonso, 1987;Marrone & Naselli Flores, 2004;Alonso & Garcia-de-Lomas, 2009;Caramujo & Boavida, 2010), not only for crustaceans but also for plants (Bagella et al, 2010). Their analysis included individuals collected by us and revealed that the population from Cavall (one of our ponds) clustered together with other populations of the H. ingens species group from localities in Italy and Corsica, while that from Sinarcas (another of our ponds) is an independent evolutionary lineage only found in this pond.…”
Section: Special Ponds With Hemidiaptomus: the Role Of Historical Facmentioning
confidence: 99%
“…Many temporary wetlands are used for watering and grazing (Bouahim et al, 2015;Croel & Kneitel, 2011a;Schmutzer, Gray, Burton, & Miller, 2008) so research increasingly focuses on the effects of grazing on wetland plant and animal communities and ecosystem function (e.g. Bagella et al, 2010;Bouahim et al, 2010;Boughton, Quintana-Ascencio, Bohlen, Fauth, & Jenkins, 2016;Marty, 2005;Pyke & Marty, 2005;Rhazi, Rhazi, Grillas, & El Khyari, 2006). For example, livestock grazing can vary along an intensity gradient (Davidson et al, 2017;Epele & Miserendino, 2015), resulting in detrimental or beneficial effects on pond biodiversity (Bouahim et al, 2010;Davidson et al, 2017;Epele & Miserendino, 2015;Marty, 2005;Schmutzer et al, 2008).…”
Section: Introductionmentioning
confidence: 99%